Robotic-assisted total knee arthroplasty: Systematic review of surgical assist robotic systems available in Japan - Keizo Wada; Daisuke Hamada; Yasuaki Tamaki; Shota Shigekiyo; Koichi Sairyo (Journal of Joint Surgery and Research)
Purpose: Surgical assistant robots are now available for total knee arthroplasty (TKA). This review aimed to clarify the characteristics, accuracy, learning curve, and clinical results of robotic-assisted (RA) TKA performed using systems that are currently available in Japan (MAKO, ROSA, NAVIO/CORI, and VELYS). Methods: The PubMed database was searched to identify studies on RA-TKA. Results: MAKO is a semi-active robot using an oscillating saw. It is a computed tomography-based platform capable of determining the size and location of an implant pre-operatively. ROSA offers both imageless and image-based options using two-dimensional radiographs that are transformed into a three-dimensional model of the knee. NAVIO and CORI are handheld robotic platforms that support image-free anatomic data collection and streamlined intra-operative surgical planning with dynamic gap balancing. VELYS is an image-free, operating room bedrail-mounted, RA system that positions an oscillating saw for the surgeon to perform bone resection with real-time cut-plane tracking to compensate for any leg movement. Although there are some characteristic differences among the surgical assistant robots, the present review reveals that robot-controlled osteotomy may be more accurate than conventional techniques using a conventional guide and bone saw, with favorable short-term outcomes after RA-TKA. Conclusions: This review found that the robotic systems recently made available in Japan demonstrate a high level of accuracy and show favorable short-term outcomes.